Effect of the frequently used antiepileptic drugs carbamazepine, gabapentin, and pregabalin on the pharmacokinetics of edoxaban and other oral factor xa inhibitors in healthy volunteers - Alexander Lenard; Simon A. Hermann; Felicitas Stoll; Juergen Burhenne; Kathrin I. Foerster; David Czock; Gerd Mikus; Andreas D. Meid; Walter E. Haefeli; Antje Blank (Frontiers in Pharmacology)
PurposePregabalin, gabapentin, and carbamazepine, a potent inducer of cytochrome P450 (CYP) 3A4 and P-glycoprotein, are frequently used antiepileptic drugs that are often administered together with factor Xa inhibitors (FXaI). We aimed to investigate whether potentially clinically relevant drug-drug interactions occur with these combinations.MethodsIn an open-label fixed-sequence trial in 36 healthy volunteers, we evaluated the pharmacokinetics of 60 mg edoxaban and of a microdosed FXaI cocktail (25 µg apixaban, 50 µg edoxaban, and 25 µg rivaroxaban) before and during treatment with carbamazepine (12 evaluable volunteers, individually dosed to therapeutic concentrations), gabapentin (11 volunteers, titrated to 3 × 400 mg/d), and pregabalin (12 volunteers, titrated to 2 × 300 mg/d). The antiepileptics were dosed to steady-state and the CYP3A activity was evaluated by assessing the pharmacokinetics of microdosed midazolam (30 µg).ResultsCarbamazepine reduced the area under the plasma concentration-time curve (AUC∞) of 60 mg edoxaban by a factor of 0.48 (geometric mean ratio (GMR) with 90% CI (0.41–0.56); p < 0.0001) and Cmax by a factor of 0.47 (0.34–0.66) and reduced the exposure of the edoxaban metabolite M-4 to a similar extent. Carbamazepine also decreased the exposure (AUC∞) of microdosed apixaban, edoxaban, and rivaroxaban by a factor of 0.66, 0.59, and 0.56, respectively. Gabapentin and pregabalin did neither affect the exposure of 60 mg edoxaban nor the exposure of any microdosed FXaI.ConclusionCarbamazepine decreased FXaI exposure to a clinically relevant extent and dose adjustment may be required to maintain an adequate anticoagulant effect, whereas gabapentin and pregabalin do not require dose adjustment of FXaI.